Future dry-wet climatic characteristics and drought trends over arid Central Asia - Cao, Linlin; Xu, Changchun; Suo, Nanji; Song, Lingling; Lei, Xiaoni (Frontiers in Earth Science, 2023)
Understanding the future drought condition is critical to coping with the challenge of climate change. This study evaluated the simulation capability of 30 Global Climate Models (GCMs) provided by the Coupled Model InterComparison Project Phase 6 (CMIP6) in simulating precipitation (P), potential evapotranspiration (PET) and temperature (T) in arid Central Asia (ACA), and estimated the dry-wet climatic characteristics and trends under four SSP-RCPs (Shared Socio-economic Path-Representative Concentration Path scenarios, SSP126, SSP245, SSP370 and SSP585). Results show that the 30 CMIP6 GCMs have robust simulation ability for P, PET and T (P<0.01) over ACA. The delta-corrected multi-model ensemble mean (Delta-MME) outperforms GWR-corrected one (GWR-MME) and single models. In the future, the P, PET and T will increase at different rates under the four SSP-RCPs. Uzbekistan, Kazakhstan, Kyrgyzstan and Tajikistan are the regions with faster P and T rise, and the northern of ACA are the main area with the rapid growth of PET. ACA will face more severe drought, especially under high emission scenarios. The near-term drought relief will not offset the increase of drought in mid and long term. In the near-term the drought will reduce at a certain extent, but the trend of drought will still be prominent in the mid and long term. Overall, drought in ACA will show an overall characteristic of decreasing DN but increasing DF, DD and DI. Drought risk is likely to be higher in Xinjiang of China, Turkmenistan and Uzbekistan. The research can provide a scientific basis for the decision-making of water resources planning and management and socio-economic development of ACA.